POTENTIAL OF RICE (Oryza spp.) STRAW AS FODDER FOR WEST AFRICAN DWARF SHEEP (2014)
Conventional feedstuffs have not met the increasing demand of livestock industry. Rice plant, a food-feed cereal, can provide grains for humans and fodder for livestock. The potential of Rice Straw (RS) as fodder for sheep in Nigeria has not been adequately documented. Therefore, the potential of RS as fodder for West African Dwarf (WAD) sheep was investigated in this study. Using Lattice design, 49 rice varieties of five cultivars: Interspecific Upland (IU), Interspecific Lowland (IL), Oryza sativa Upland (OsU), Oryza sativa Lowland (OsL) and Oryza glaberrima (Og) were assessed in hydromorphic ecology for Grain Yield (GY tonne/ha), Straw Yield (SY tonne/ha), Harvest Index (HI), Tillers Per Square Metre (TPSM) and Plant Height (PH). Straw samples were analysed for nitrogen, Neutral Detergent Fibre (NDF), Acid Detergent Fibre (ADF), Metabolisable Energy (ME), in-vitro Organic Matter Digestibility (OMD), ash and silica contents using standard procedures. In a completely randomised design, 20 WAD rams were used to assess Voluntary Dry Matter Intake (VDMI) and Dry Matter Digestibility (DMD) of NERICA-14 (IU), NERICA-Lowland-20 (IL), ITA-321 (OsU), Cisadane (OsL) and CG14 (Og). Data were analysed using descriptive statistics and ANOVA at α0.05. The GY of IL (3.6±1.0) and OsL (3.6±1.2) were higher than for IU (2.1±0.9), OsU (2.2±1.0) and Og (1.7±0.7). The SY of Og (5.0±2.6) was similar to 4.6±1.6 for OsL, but higher than 4.2±1.5, 2.7±1.0 and 3.0±1.2 for IL, IU and OsU, respectively. The HI of IL (0.46±0.07) was similar to 0.44±0.08 (OsL) but higher than 0.43±0.09 (IU), 0.42±0.09 (OsU), and 0.28±0.11 (Og). The TPSM of the cultivars ranged from 161.7 m-2 to 493.8 m-2, with Og having the highest value of 493.8±207.4 m-2. The PH of the cultivars ranged from 102.2 to 124.0 cm, with Og and OsU having higher values of 124.0±34.2 cm and 122.5±19.9 cm, respectively. Nitrogen of IL (0.91±0.28 %), IU (0.89±0.32 %) and OsU (0.87±0.32 %) were similar but higher than 0.82±0.31 % (OsL) and 0.83±0.24 % (Og). The NDF of OsL (67.1±2.5 %) was similar to Og (66.7±3.9 %), OsU (66.6±2.5 %) and IU (66.4±2.3 %); but higher than that of IL (65.9±2.5 %). The ADF and ME ranged from 48.7-51.5 % and 6.1-6.7 MJ/kg, respectively. The OMD of IU (46.1±5.3 %) and OsU (46.7±5.8 %) were significantly higher than values for OsL (44.6±6.1 %), IL (44.9±5.9 %) and Og (43.6±4.3 %). The ash content of IL (18.6±0.4 %), IU (18.8±0.3 %) and Og (19.4±0.7 %) were higher than 17.7±0.5 % and 17.6±0.5 % for OsU and OsL, respectively. The silica content of Og, 14.3±0.5 % was similar to 13.7±0.2 % for IU but higher than 13.4±0.3 %, 13.2±0.4 % and 12.9±0.3 % for IL, OsU and OsL, respectively. The VDMI (47.9-57.4 gKg-1BW0.75day-1) and DMD (30.2-44.7 %) of WAD rams were similar among the varieties. The grain and straw yields for the rice varieties were high. The voluntary dry matter intake and dry matter digestibility for sheep fed straws of the five representative rice varieties established the potential of rice straw as fodder for West African dwarf rams. Keywords: West African dwarf rams, Food-feed cereal, Fodder crop, Voluntary dry matter intake, Oryza spp. Word Count: 500